[RETRACTED] PSYCHO-EMOTIONAL STATUS IN PATIENTS WITH INFLAMMATORY BOWEL DISEASE: This article has been retracted. The editorial board of the journal has determined that the article contains textual borrowings that are translations of foreign-language articles (parts thereof) without appropriate references to them. The decision to retract the article is based on the international COPE guidelines and was made in accordance with the publication ethics and editorial policy of the journal. The corresponding author agreed to the retraction of the article. - Romanukha , Viktoriya; Hryniv, Olena; Hvozdetska, Halyna; Baryla, Nadiia; Hrushetska , Anna (Eastern Ukrainian Medical Journal, 2024)
Introduction. Inflammatory bowel disease is a chronic disease of unclear etiology, with periods of exacerbation and remission, has negative social, physical and emotional consequences and reduces quality of life. It is an obvious fact that psychological status and quality of life are influenced by a significant number of factors, including the disease itself (Crohn's disease is most often more severe, especially in young patients), the severity of the disease, the prevalence of digestive tract involvement, extraintestinal manifestations, complications, surgical interventions and the effectiveness of the chosen therapy.Materials and methods. The literature review was based on scientific studies published by Science Direct using the information retrieval systems PubMed, Web of Science, Scopus, Google Scholar, The Cochrane Librar, Medknow. We mainly reviewed the studies that were published in the last 5 years. 68 scientific papers were selected for the article.Results After analysing the sources of national and international literature, the risk factors (poor sleep quality, reduced physical activity, fatigue, female gender, obesity, intestinal dysbiosis, surgery with stoma formation) that contributed to a negative impact on the patient's quality of life were identified. Possible methods to alleviate psychopathological symptoms, namely psychotherapy, medication and regular physical activity, were described.Conclusions. Inflammatory bowel disease contributes to the development of depressive and anxiety disorders, asthenia, sexual dysfunction, poor sleep quality, reduced physical activity, work quality, and productivity. The use of psychotherapy, namely cognitive behavioural therapy, psychodynamic therapy, acceptance and commitment therapy, stress management programs, mindfulness, hypnosis, antidepressant medication and regular physical activity, leads to an improvement in the patient's quality of life.